LAB DEMONSTRATOR APPLICATION AND SELECTION MANAGEMENT SYSTEM (DEMOSYS) - Vynalyn, Ellen (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The rapid changing of technologies usage in human routine lifestyle has tremendously changed how an organization organizations works in order to survive in the competitive worlds. Before the technologies advancement, using manual processes in managing and organizing the information and data. But after moving towards the information technologies age, most organization turning into computerizing processes in order to manage and handle their information and data. Hence, the process changed has given advantages such as improving the productivity, efficiency, and effectiveness as well as better in handling the organization information. Nowadays, the Internet revolutions has become an important medium for organization of global business and media electronics that deliver and sharing resources in a faster and effective ways. Demosys is focused on computerizing the manual system existing for lab demonstrator application form, processes and selection management system by the lecturer. This system eliminates the paper based record keeping with computer, provides electronic application online that easily access, and helping in making the selection of lab demonstrator. Demosvs is using open source scripting language Hypertext Preprocessor (PHP) that is especially suited for weh development that can he embedded into Hypertext Markup Language (HTML). The Apache is used which acts as the server in order to test the application system. Demosvs using MySQL which is an open source database management system that relies on Structured Query Language (SQL) for processing the data in the database. It is commonly used for weh applications and for embedded applications and has become a popular alternative to proprietary database systems because of its speed and reliability. As a conclusion, the development of Demos vs served as weh based system that helps both the lecturer and student of Faculty of Computer Science and Information Technology in lab demonstrator application and selecting the lab demonstrator